Social Change and Modernity: Identity Crisis of the Bonda Tribe in Pratibha Ray’s The Primal Land - Chitra, S.; Tenzin, Sangay (SCHOLARS: Journal of Arts & Humanities, 2021)
Pratibha Ray’s anthropological novel The Primal Land (1993) documents the history of India’s endangered Bonda tribe dwelling in the secluded mountains of Koraput, Odisha. Not free from the interferences of the outside world, the Bondas face the threat of losing their tribal identity. This complicated position and their struggle between existence and identity, an intersubjective reality, was triggered by oppressive internal and external surroundings due to the pressures of modernity. The discussion focuses on their inherent cultural practices causingconstant internal feuds and the government’s intrusion with development plans leading to exploitation, cultural dilution, and socio-ethnic tension. Thus the paper decodes the difficulties of the Bondas and concludes that their existence cannot be ensured without the loss of primal identity.